Randomised clinical trial using Coronary Artery Calcium Scoring in Australian Women with Novel Cardiovascular Risk Factors (CAC-WOMEN Trial): study protocol. Issue 12 (22nd December 2022) - Marschner, Simone; Wing-Lun, Edwina; Chow, Clara; Maple-Brown, Louise; Graham, Sian; Nicholls, Stephen J; Brown, Alex; Wood, Anna; Ihdayhid, Abdul; Von Huben, Amy; Zaman, Sarah
Abstract : Introduction: Cardiovascular disease (CVD) is the leading cause of death in women around the world. Aboriginal and Torres Strait Islander women (Australian Indigenous women) have a high burden of CVD, occurring on average 10–20 years earlier than non-Indigenous women. Traditional risk prediction tools (eg, Framingham) underpredict CVD risk in women and Indigenous people and do not consider female-specific 'risk-enhancers' such as hypertensive disorders of pregnancy (HDP), gestational diabetes mellitus (GDM) and premature menopause. A CT coronary artery calcium score ('CT-calcium score') can detect calcified atherosclerotic plaque well before the onset of symptoms, being the single best predictor for future cardiac events. A CT-calcium score may therefore help physicians intensify medical therapy in women with risk-enhancing factors. Methods and analysis: This multisite, single-blind randomised (1:1) controlled trial of 700 women will assess the effectiveness of a CT-calcium score-guided approach on cardiovascular risk factor control and healthy lifestyle adherence, compared with standard care. Women without CVD aged 40–65 (35–65 for Aboriginal and Torres Strait Islander women) at low-intermediate risk on standard risk calculators and with at least one risk-enhancing factor (eg, HDP, GDM, premature menopause) will be recruited. Aboriginal and Torres Strait Islander women will be actively recruited, aiming for 10% of the sample size. The 6-month coprimary outcomes will be low-density lipoprotein cholesterol and systolic blood pressure. Barriers and enablers will be assessed, and a health economic analysis performed. Ethics and dissemination: Western Sydney Local Health District Research Ethics Committee (HREC 2021/ETH11250) provided ethics approval. Written informed consent will be obtained before randomisation. Consent will be sought for access to individual participant Medicare Benefits Schedule, Pharmaceutical Benefits Scheme claims usage through Medicare Australia and linked Admitted Patient Data Collection. Study results will be disseminated via peer-reviewed publications and presentations at national and international conferences. Trial registration number: ACTRN12621001738819p.